Uncle Billy's wine guide for novices - Kritsonis, William Allan; Smith, Ann Marie (Wine novice) (Emerald Publishing Limited : Information Age Publishing, Inc., 2020)
Uncle Billy's Wine Guide for Novices is not intended for wine experts and others that consider themselves extremely knowledgeable about wine. This book is for the rest of us who want to learn more about the pleasures of enjoying wine and talking intelligent about it.About 8% of wine consumers consider themselves extremely knowledge about wine. Of these, about 3% consider themselves wine experts. This leaves the rest of us, about 92% who want to learn more about wine but don't want to become experts.Humor is scattered throughout the book to make your reading more enjoyable. The goal is to help you become more knowledgeable about wine and have fun doing so. And remember: "Always drink the wine you enjoy, and enjoy the wine you drink." William Allan Kritsonis, PhD, Author.